Une grande hydraulique saharienne à l’époque médiévale - Chloé Capel (Mélanges de la Casa de Velázquez, 2016)
While the caravan trade provided the bulk of the wealth behind the expansion of the mediaeval town of Sijilmassa (Morocco) around the 8th and 9th centuries, it is no less true that the development of its agricultural hinterland was another essential factor in its urban growth. The Sijilmassa oasis is strictly associated with the exploitation of a oued: the Ziz. It is more than fifty years since it was established that this oued was man-made, is in fact a canal, but this singularity never drew the attention of historians and archaeologists despite the social, technical and cultural implications implicit in such a subject of study. Nevertheless, by placing this geological discovery in an archaeological and historical perspective we can open up new avenues for exploration of the history of power, economics, agriculture, technical know-how and exchange of knowledge, in Sijilmassa itself, but also more generally on the fringes of the Maghreb during the early centuries of Islam.